URGENSI PENDIDIKAN KEMANDIRIAN TERHADAP ANAK DALAM PERSPEKTIF HADITS TARBAWI / THE URGENCY OF INDEPENDENCE EDUCATION FOR CHILDREN FROM THE TARBAWI HADITH PERSPECTIVE - Rosi Tunas Karomah; Lailatu Rohma; Khamim Zarkasih Putro (Al-Mudarris: Journal Of Education, 2024)
The level of independence of children that is often found today is still relatively low in carrying out daily activities. Independence itself was taught during the time of the Prophet in his personal life. It is important to teach independence education to young children according to the tarbawi hadith perspective. Library research is the method carried out in this research. The results of this research are that it is very important to teach independence education to young children so that they have the habit of not depending on other people, trying to achieve what they want and having an independent mentality that encourages them to help others. The implications of this research are to open the eyes of educators and parents in intensifying children's independent activities. Independence education needs to be taught to children for their continuation and readiness to face the challenges that will be faced both in terms of academics and in the social environment. Self-reliance education has also been applied by the Prophet SAW since he was a child to adolescence, starting from herding goats owned by others to becoming a trader with his uncle in his teens. Independence has a positive impact on one's life starting from practicing self-confidence, Help someone overcome the problems faced, not easily discouraged, have high sympathy and empathy, easy to get along and socialize in a new environment. As well as having a strong mentality in facing existing challenges.